Hepatic artery and biliary complications in liver transplant recipients with radioembolization bridging treatment for hepatocellular carcinoma. Issue 11 (17th September 2017) - Radunz, Sonia; Saner, Fuat H.; Treckmann, Jürgen; Rekowski, Jan; Theysohn, Jens M.; Müller, Stefan; Best, Jan; Sotiropoulos, Georgios C.; Paul, Andreas; Benkö, Tamás
Abstract: Background: Locoregional bridging treatments are commonly applied in patients with hepatocellular carcinoma (HCC) prior to liver transplantation to prevent tumor progression during waiting time. It remains unknown whether pre‐transplant radioembolization treatment may increase the prevalence of hepatic artery and biliary complications post‐transplant. Methods: We performed a retrospective review of 173 consecutive patients with HCC who underwent liver transplantation at our transplant center between January 2007 and December 2016. Results: Radioembolization bridging treatment was applied in 42 patients while 131 patients received other or no forms of bridging treatment. The overall prevalence of intra‐operative and early post‐operative hepatic artery complications was 9.5% in the radioembolization group and 9.2% in the control group ( P  = 1.000). Biliary complications were significantly less frequent in the radioembolization group (4.8% vs 17.6%, P  = .0442). In multivariable analysis, radioembolization was not significantly associated with an increased risk of arterial complications. Considering biliary complications, radioembolization bridging treatment was the only factor significantly associated with decreased odds (OR 0.187 (0.039, 0.892), P  = .036). Conclusions: Radioembolization is not associated with higher odds of hepatic artery complications following liver transplantation. There may even be a protective effect regarding biliary complications. Radioembolization as a bridge to transplantation may effectively be applied without compromising successful liver transplantation.